The critical assessment of the direct referentialist solutions to the semantic problems of empty names - Polat, Mustafa. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Direct Referentialist account of proper names fundamentally contends that the sole semantic meaning of a proper name is its referent if and only if it has any. By the principle of semantic compositionality, it entails the conclusion that a proper name in a sentence is used to express a proposition if and only if it has a referent. Thus, for Direct Referentialist account, empty names such as “Santa Claus” and “Vulcan” have no semantic meaning and empty-name sentences fail to express a proposition. Considering the truth-conditional and semantic function of a proposition in the conventional sense of truth-conditional semantics, Direct Referentialism implies that empty-name sentences fail to express a meaningful and a truth-evaluable content. However, it does not jibe with our common semantic and truth-theoretical intuitions about empty-name sentences. As our linguistic intuitions suggest, empty-name sentences are meaningful and truth-evaluable. Hereby, Direct Referentialism appears to confront with the semantic problems in terms of our linguistic intuitions of what is said by an empty-name sentence. In order to divorce Direct Referentialism from the burden of being a counter-intuitive account, a number of Direct Referentialist philosophers propose distinct solutions. Nonetheless, these solutions also include theoretical flaws in terms of their explanatory efficacy and of their compatibility with the fundamental thesis of Direct Referentialist account.
Keywords: Reference (Philosophy); Language and languages -- Philosophy.